The role of mindfulness and cognitive fusion in predicting self-compassion among patients with schizophrenia: a cross-sectional study - Warda Elshahat Hamed; Nesma Ahmed Kamel; Amani Ali Kappi; Ashjan Saeed Babegi; Hamad Ghaleb Dailah; Rania Rabie El-Etreby (BMC Psychiatry)
Abstract Background The exact connection between mindfulness, psychological flexibility, and severity of symptoms within schizophrenia spectrum disorders is mostly undefined and requires additional exploration. This study aimed to determine whether mindfulness, cognitive fusion, and symptom severity predict self-compassion among patients with schizophrenia. Methods A cross-sectional descriptive research design was undertaken within the psychiatric in-patient department of Mansoura University Hospitals, situated in El-Mansoura, the administrative centre of Dakahlia governorate in the Delta area, Egypt. A total of 100 patients with schizophrenia participated in the study. Data were collected from October 2023 to January 2024 by using various tools: A socio-demographic questionnaire and clinical data sheet, the Positive and Negative Syndrome Scale (PANSS), the Mindful Attention Awareness Scale (MAAS), The Cognitive Fusion Questionnaire (CFQ), and The Self-Compassion Scale – Short Form (SCS-SF). Results The findings show that mindfulness significantly impacts self-compassion among patients with schizophrenia. The results show that mindfulness significantly and positively impacts self-compassion, and cognitive fusion significantly and negatively impacts self-compassion. However, symptom severity did not significantly impact self-compassion (B = -0.02, t = -0.56, p = 0.57). Conclusion The study concluded that people with schizophrenia need to be aware of their inner experience of negative feelings and thoughts at the moment and accept them. Thus, ACT, mindfulness-based, and compassion-based interventions may improve patients’ cognitive fusion, mindfulness, psychological flexibility, and self-compassion.